2016
DOI: 10.1007/s12020-016-1157-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulin G4 levels and Graves’ disease phenotype

Abstract: Our data suggest that Graves' disease patients with elevated immunoglobulin G4 levels at diagnosis have a phenotype characterized by higher anti-thyroglobulin antibody and antithyroid peroxidase antibody titers, less severe T3 hyperthyroidism, younger age at ophthalmopathy onset and require a shorter duration of the first methimazole treatment cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
10
1
3
Order By: Relevance
“…Based on our data, none of the factors including age, sex, duration of AITD, smoking status, the presence of ophthalmopathy, and thyroid auto-antibodies have any association with the elevated serum IgG4 levels. This was different from previous studies which reported that elevated serum IgG4 were positively correlated with the titers of thyroid auto- antibodies [27] , [28] . It should be also noted from current study that the presence or absence of ophthalmopathy did not affect the levels of serum IgG4 which our findings were contrast with Bozkirli et al [29] which found the positive correlation between serum IgG4 and severity of Graves’ ophthalmopathy.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on our data, none of the factors including age, sex, duration of AITD, smoking status, the presence of ophthalmopathy, and thyroid auto-antibodies have any association with the elevated serum IgG4 levels. This was different from previous studies which reported that elevated serum IgG4 were positively correlated with the titers of thyroid auto- antibodies [27] , [28] . It should be also noted from current study that the presence or absence of ophthalmopathy did not affect the levels of serum IgG4 which our findings were contrast with Bozkirli et al [29] which found the positive correlation between serum IgG4 and severity of Graves’ ophthalmopathy.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher IgG4 levels as well as a higher IgG4/IgG ratio also characterized patients with moderate-to-severe and/or active GO as opposed with those having mild and/ or inactive GO. In this study, serum IgG4 levels positively correlated with TRAb levels, similarly to the finding by Takeshima (38) and in contrast to those of Martin (39). Similarly to HT, also in GD, a decrease in IgG4 levels following thyroidectomy was described (41).…”
Section: Graves' Diseasesupporting
confidence: 88%
“…Indeed, this 47-year-old woman was diagnosed with Graves' hyperthyroidism and, started on MMI therapy, experienced a successful restoration of euthyroidism. More than 4 years after the initial diagnosis, and 6 months after the withdrawal of MMI, the patient developed overt hypothyroidism and, owing to the presence of a large (38), no such a correlation was found by Martin et al (39). On the other hand, the latter study reported that thyroid autoantibody-positive patients had significantly higher serum IgG4 levels compared to the negative ones.…”
Section: Graves' Diseasementioning
confidence: 79%
“…In fact, IgG4 levels do not increase with age, suggesting that some unknown factor may be responsible for the abnormal expression of IgG4. 22 We found that the IgG4-positive subtype was an independent factor associated with the active stage in patients with TED. There were more active patients and patients with a higher CAS in the IgG4-positive group than in the IgG4-negative group in our study, consistent with the conclusion presented in a previous Korean study.…”
Section: Discussionmentioning
confidence: 64%